PENGARUH MODEL QUANTUM LEARNING DENGAN FORMASI TEMPAT DUDUK CORAK TIM TERHADAP HASIL BELAJAR SISWA KELAS IV SDN KABONGAN KIDUL REMBANG - Suryaningtyas, Shinta Ayu; Khoiri, Nur; Subekthi, Ervina Eka (JGK (Jurnal Guru Kita), 2019)
Abstract: Influence of Quantum Learning Model With Sitting Formation of Team Towards Students Learning Outcomes of Class IV SDN Kabongan Kidul Rembang. This study aims to determine the effect of the application of learning model of quantum learning with the formation of the team style seating on the results of fourth grade students of SDN Kabongan Kidul Rembang. This type of research is quantitative research type experiment with pre-experimental design type that is onegroup pretest-posttest design. The population of this research is the fourth grade students at SDN Kabongan Kidul Rembang. The sample of this research is all students of grade IV SDN Kabongan Kidul Rembang academic year 2017/2018 which amounted to 35 students. Data collection using interviews, tests, observations and documentation. The research results obtained pretest average of 59.65 while the average posttest of 83.71. So it can be concluded that the quantum learning model with the formation of the seating pattern of the team has an effect on the students’ achievement of fourth grade SDN Kabongan Kidul Rembang. Keyword : Quantum Learning Model, Seating Formation, Learning Outcomes Abstrak : Pengaruh Model Quantum Learning Dengan Formasi Tempat Duduk Corak Tim Terhadap Hasil Belajar Siswa Kelas IV SDN Kabongan Kidul Rembang. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan model pembelajaran quantum learning dengan formasi tempat duduk corak tim terhadap hasil belajar siswa kelas IV SDN Kabongan Kidul Rembang. Jenis penelitian ini adalah penelitian kuantitatif tipe eksperimen dengan jenis pre-experimental design yakni one-group pretest-posttest design. Populasi penelitian ini adalah siswa kelas IV di SDN Kabongan Kidul Rembang. Sampel penelitian ini yaitu semua siswasiswi kelas IV SDN Kabongan Kidul Rembang tahun ajaran 2017/2018 yang berjumlah 35 siswa. Pengambilan data menggunakan wawancara, tes, observasi dan dokumentasi. Hasil penelitan diperoleh rata-rata pretest yaitu sebesar 59,65 sedangkan hasil rata-rata posttest sebesar 83,71. Jadi dapat disimpulkan model quantum learning dengan formasi tempat duduk corak tim berpengaruh terhadap hasil belajar siswa kelas IV SDN Kabongan Kidul Rembang. Kata Kunci : Model Quantum Learning, Formasi Tempat Duduk, Hasil Belajar